Hot Topics on COVID-19 and Its Possible Association with Guillain-Barré Syndrome - Dietmann, Anelia; Ripellino, Paolo; Humm, Andrea M.; Hundsberger, Thomas; Schreiner, Bettina; Théaudin, Marie; Scheidegger, Olivier (Clinical and translational neuroscience, 2022)
As the COVID-19 pandemic progresses, reports of neurological manifestations are increasing. However, despite a high number of case reports and case series on COVID-19 and Guillain-Barré-Syndrome (GBS), a causal association is still highly debated, due to the lack of case-control studies. In this opinion paper, we focus on a few clinically relevant questions regarding the possible link between GBS and SARS-CoV-2 infection or vaccination based on our personal clinical experience and literature review.